Gender‐related differences on short‐ and long‐term outcomes of patients undergoing transcatheter aortic valve implantation. Issue 3 (29th July 2016) - Katz, Marcelo; Carlos Bacelar Nunes Filho, Antonio; Caixeta, Adriano; Antonio Carvalho, Luiz; Sarmento‐Leite, Rogério; Alves Lemos Neto, Pedro; Eduardo Koenig São Thiago, Luiz; Dias Dourado Oliveira, Adriano; Antonio Marino, Marcos; Tadeu Tumelero, Rogerio; Antonio Perin, Marco; Abizaid, Alexandre; et al.
Abstract : Objectives: This study aimed to compare gender‐related differences in outcomes of patients undergoing TAVI over a long‐term follow‐up period. Background: Transcatheter aortic valve implantation (TAVI) has been considered the standard therapy for patients with inoperable or high‐risk symptomatic aortic stenosis. The influence of gender‐related differences in outcomes of patients undergoing TAVI is currently on debate. Methods: From January 2008 to January 2015, 819 patients (49% men) underwent TAVI and were included in a multicenter Brazilian registry. Patients were followed‐up and clinical outcomes were evaluated according to the updated Valve Academic Research Consortium‐2 criteria. Results: Mean follow‐up was 497 ± 478 days. Compared with women, men had a lower rate of major or life‐threatening bleeding (12.0% vs. 20.6%; HR = 0.57 [95CI% 0.40–0.81]; P = 0.001), and major vascular complications (6% vs. 11.7%; HR = 0.50 [95CI% 0.31–0.82]; P = 0.004). At 30 days, all‐cause mortality was lower in men than in women (6.5% vs. 11.5%; P = 0.013), however, cumulative all‐cause mortality was similar between groups (25.9% vs. 29.7%, men and women, respectively, HR = 0.92 [95CI% 0.71–1.19]; P = 0.52) over the entire follow‐up period. By adjusted Cox regression model, renal function, diabetes, peripheral artery disease, and chronic obstructive pulmonary disease (COPD) remained independently predictors of all‐cause mortality. Conclusions: In this large‐scale study evaluating patients undergoing TAVI, 30‐day mortality was higher among women than men driven by significant higher rates of major or life‐threatening bleeding and major vascular complications. However, all‐cause mortality on long‐term follow‐up was similar between groups. © 2016 Wiley Periodicals, Inc.